MODERATED ANALYSIS OF CORPORATE VALUES INSTITUTIONAL OWNERSHIP (CASE STUDY OF FOOD & BEVERAGE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017-2021) - Pambudi, Agung; Mohklas, Mohklas; Andini, Rita (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
The purpose of this study was to determine the effect of Profitability on Company Value, Leverage on Firm Value, Company Size on Company Value, Profitability on Firm Value mediating Institutional Ownership, Leverage on Company Value mediating Institutional Ownership, and Company Size on Company Value mediating ownership. institutional. The sample was selected using the purposive sampling method by producing 23 food and beverage company data, so that the total research data for 5 years 2017-2022 was 115 samples. The data analysis technique uses multiple linear regression and Moderate Regression Analysis.